Transformation of Digital Communication Media in Practicum-Based Learning: Examining the Experience of IAIN Langsa Lecturers, Aceh - Rusli Rusli (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
The transformation of communication in education is critical to sustaining good learning. The COVID-19 epidemic has altered how instructors communicate, hence changing their body of knowledge. This study explores how instructors at IAIN Langsa, Aceh, have dealt with the shift from traditional to digital communication media in the context of teaching. The primary emphasis is on how they modified their communication tactics to manage learning following the COVID-19 outbreak and the difficulties they encountered, such as shifting learning paradigms and gaining access to technology. This study uses a qualitative methodology to show how lecturers' personal experiences in practicum courses mirror efforts to enhance learning connections in this new era. Interviews with practicum course teachers who continue to employ digital media for instruction served as the data source. The study's findings demonstrate that lecturers' communication styles have changed during the teaching and learning process. Lecturers mostly communicate via the Zoom program, while attempts are being made to use alternative platforms, including Google Classroom and WhatsApp. They still have significant difficulties with communication regularity and frequency, though. to boost lecturers' digital literacy and the efficacy of communication education through media diversity. After the COVID-19 pandemic, IAIN Langsa's communication media underwent a quick metamorphosis; nonetheless, additional work must be done to support an ideal learning experience with more effective communication.